Everyday Precarities and Systemic Exploitations: Indonesian Migrant Workers in Sarawak's Palm Oil Industry - Vilashini, Somiah; Hashim, Haslina; Aishah Mutmainnah, Khairul Annuar; Farah Izzati, Hanip (UNIMAS Publisher, 2025)
The Malaysian palm oil industry is a cornerstone of the nation’s economy, yet it faces a critical labour shortage, particularly in Sarawak, exacerbated by the COVID-19 pandemic and migration barriers. A significant portion of the workforce in Malaysia’s palm oil plantations comprises Indonesian migrant workers, many of whom are undocumented. This study explores the role of undocumented Indonesian migrant labour in addressing the labour shortages in Sarawak's palm oil sector, focusing on the systemic challenges these workers face. Through in-depth interviews with 15 undocumented migrant workers and 5 key informants, this qualitative research highlights the legal, social, and economic vulnerabilities that contribute to exploitation and poor working conditions. The study reveals the complexity of migration patterns, the predominance of male workers in physically demanding roles, and the exploitation facilitated by undocumented status. Additionally, the research uncovers the gendered divisions of labour that limit women’s participation in core plantation tasks. The research contributes to a deeper understanding of the systemic challenges facing the palm oil industry in Sarawak and underscores the need for policy reforms to protect migrant workers’ rights and improve labour conditions. By focusing on Sarawak, this study adds a critical perspective to the broader discourse on migrant labour in Malaysia, particularly in regions often overlooked in existing literature.